Examining the Acceptance of Virtual Reality Integration in Malaysian Aircraft Maintenance Training - Ong, Yuan Sheng; Selimin, Mohamad Ali; Abdul Hamid, Nor Aziati (Research in Management of Technology and Business, 2026)
Virtual Reality (VR) is a computer-generated technology that enables users to interact with a simulated environment. Increasingly adopted across industries for training purposes, VR has demonstrated the potential to transform traditional training approaches by replacing real-world exercises with immersive virtual experiences. This study investigates the level of acceptability and the effects of VR-based training within Malaysian aircraft maintenance training programmes. Compared to conventional methods, VR-based training offers two primary advantages: enhanced safety through risk-free simulation of high-risk scenarios, and cost-effectiveness by reducing reliance on physical resources and infrastructure. Using a structured survey administered to respondents from Canadian Aviation Electronics (CAE) in Kuala Lumpur, Malaysia, this research aims to determine the level of VR technology acceptance among trainees and trainers and to evaluate its overall impact. The study applies the Technology Acceptance Model (TAM) to identify key factors influencing VR adoption, including perceived ease of use, perceived usefulness, attitudes toward VR, and intentions to use. Data analysis was conducted using SPSS, encompassing reliability analysis, descriptive statistics, normality tests, and correlation analysis. The findings indicate that all three TAM constructs exhibit a significant positive correlation with the acceptability of VR-based training, with correlation values falling between 0.345 and 0.463. These results address existing research gaps and offer practical recommendations for integrating VR into maintenance training, providing valuable insights for training providers, policymakers, and industry stakeholders in Malaysia.